Household Waste Management and Practice among the Residents of Makama Jahun Ward Bauchi Metropolis, Bauchi State, Nigeria - Salisu Umar Muhammad; Abubakar Yawa Wakeh; Mubarak Ibrahim Ahmad (Balai Publikasi Indonesia, 2026)
The study focused on household waste management practices among residents of Makama Jahun, Bauchi Metropolis. Three objectives with three corresponding research questions were formulated. The primary aim of the study is to assess the factors influencing household waste management and practices in Makama Jahun, Bauchi. The specific objectives are: To examine various method of waste disposal among the residents of Makama Jahun, to identify the environmental factors that contribute to indiscriminate waste disposal and to find out the effects of indiscriminate waste disposal in Makama Jahun, Bauchi Metropolis This study aims to improve waste management practices to mitigate negative implications and create a cleaner and healthier environment in Makama Jahun, Bauchi. A test-retest method was employed, and the data were administered with the help of an assistant. The collected data were presented in frequency distribution tables and analyzed using simple percentages. Key findings revealed that 75% of respondents believed that seasonal variations contribute to indiscriminate waste disposal, while 55% did not consider the lack of infrastructure as a contributing factor. The study concludes that indiscriminate waste disposal in Makama Jahun leads to unsanitary conditions and environmental pollution, exacerbated by irregular municipal waste services and various environmental factors. Recommendations include educating the community on the dangers of improper waste disposal, supporting markets for recycled materials, and implementing government policies to prevent waste generation. Further research is suggested to replicate this study in other wards to provide broader insights.